Dynamiques réglementaires et planifications des firmes : les leçons des limites d’émissions de polluants dans l’automobile - Samuel Klebaner (Revue de la Régulation)
The aim of this thesis is to understand the institutional mechanisms that drive a manufacturing firm to act on and react to regulations. We construct first a methodological framework based on the theory of fields that can analyze both regulatory dynamics and affected industrial dynamics. Second, we elucidate this double dynamic by empirically studying the European car makers’ trajectories in relation to the air pollutants emissions regulation. We then elucidate its genesis and dynamics, highlighting the role of institutions and actors in the rule-making processes. Then, we show how air pollutants emissions limits are incorporated into the planning process of the car manufacturers’ activities. To conclude, we show that the uncertainty produced by the interactions and inadequacies between the regulations dynamics and the planning activities imply nondeductible ex ante behaviors.